Pulmonary Function Tests in Coronavirus Disease 2019 Pandemic: The Thoughts and Concerns of the Patients - Vardaloğlu, Ilgım; Börekçi, Şermin; Tombul, Kamile; Enşen, Nihal; Can, Günay; Gemicioğlu, Bilun (Cerrahpaşa Medical Journal, 2024)
Objective: Due to the risk of transmission in the coronavirus disease 2019 (COVID-19) pandemic, the pulmonary function test (PFT) could not be applied for a certain time. Guidelines on the functioning of PFT laboratories in pandemic have been prepared from the perspective of health professionals, and it has not been investigated whether these guideline recommendations are in line with the expectations of patients. In this study, it was aimed to investigate the perspectives of the patients who underwent PFT during the pandemic on compliance with the guidelines. Methods: A cross-sectional study conducted at the pulmonary function laboratory between June and September 2021. Patients filled out “COVID-19 Perception Scale” and “COVID-19 Avoidance Attitudes Scale” before the PFT, and “Patients’ view of PFT during the COVID-19 period survey” after the test. Results: The mean age of 201 participants was 45.87 of the participants (43%) agreed that their concerns about undergoing PFT had increased compared to pre-COVID period. Eighty-six percent of patients agreed that COVID polymerase chain reaction (PCR) should be given before the test, and 50% of the participants agreed that COVID PCR should be given after the test. The survey of patients’ views total score of patients receiving outpatient COVID-19 treatment was found significantly higher. Conclusion: Although there are delays in the diagnosis and treatment processes because of the prolongation of the PFT processes due to the safety measures taken in line with the guidelines prepared from the perspective of healthcare professionals, these measures are necessary and sufficient from the patients’ perspective. Cite this article as: Vardaloğlu I, Börekçi Ş, Tombul K, Enşen N, Can G, Gemicioglu B. Pulmonary function tests in coronavirus disease 2019 pandemic: The thoughts and concerns of the patients. Cerrahpaşa Med J. 2024;48(1):81-87.